Competition effects of date of sowing and nutsedge removal time on yield and yield contributing characters of tef [Eragrostis tef (Zucc.) Trotter] - Juraimi, Abdul Shukor; Begum, Mahfuza; Sherif, Ahmed Mohammed; Abdul Rahim, Anuar (Science Publications, 2009)
Problem statement: Tef [Eragrostis tef (Zucc.) Trotter] is a C4 grass, most important indigenous cereal crop in Ethiopia. The average grain yield of this crop is low; averaging <0.8 Mg ha-1. Under appropriate cultural practices such as the right sowing date, sowing rate, weeding time and fertilizer application, tef could produce grain yields of 2200-4599 kg ha-1. A delay in planting beyond recommended date a substantial yield reduction might be occurred. On the other hand, surveys showed that purple nutsedge (Cyperus rotundus L.) is a noxious weed present in varying abundance in tef. Yield loss due to nutsedge alone could be as high as 42% in agronomic crops. In addition, tef as well as purple nutsedge possesses the highly efficient C4 dicarboxylic acid photosynthetic pathway, which enhances their potential as high yielding crops or serious weeds. Studies on competitive ability of tef with improved cultural practices would provide more effective weed suppression and economic benefits to famers in Ethiopia, where chemical control is economically not feasible. The competitive effect between tef and purple nutsedge, both C4 species, has not been studied yet. Hence, this paper deals with the effects of delay in tef sowing date and nutsedge removal time on growth and yield of tef. Approach: Tef was planted at three sowing dates, recommended sowing date, 7 and 15 days delay after the recommended date. The five weed removal time were included as weedy check (W1), weeded 2 weeks (W2), 4 weeks (W3), 6 weeks (W4) after crop emergence and weed-free check (W5). All data were subjected to analysis by SAS, correlation/regression analysis and treatment means were compared using Tukeys Test. Results: Weed removal time played a minor role compared to sowing time. Irrespective of weeding dates, delayed tef sowing was very critical. When sowing was delayed for 7 and 15 days, reduction of plant height by 6.97 and 11.53%, panicle length by 8.21 and 12.32% and grain yield by 15 and 16%, respectively There was relationship among plant height, biomass and grain yield, where by grain yield responds positively to taller plants and higher biomass when the crop is sown early in the season. Hence, tef was more competitive than nutsedge. Early sowing of tef is essential to increase crop growth and yield. Conclusion/Recommendations: Increase in plant height, panicle length and a corresponding increase in tef grain yields, provided that there was no delay in sowing of tef at all.